Using Inclusive Language in the Applied-Science Academic Environments - Taheri, Pooya (Technium Social Sciences Journal, 2020)
Language is not neutral or used in a vacuum; language is one of the most powerful tools we have as humans that incorporates personal assumptions, social norms, and cultural ideologies. It is therefore important to consider language critically and to watch for biases in usage. Language reflects the world it is used in, but it is also active in maintaining or redesigning that world. It can be a tool of discrimination or of empowerment. We can use it to foster discrimination, unintentionally or otherwise, or we can use it to help make a fairer world [1]. Words have the power to affect our personhood, our identity, our attitudes, and our images about others. The power of language to affect our identity and behaviour was realized by oppressed groups in the 20th Century. Language is an important part of socialization - it plays a crucial part in the process whereby people learn the behaviours and values of a particular group or culture [2]. Historically, language has left many out. Individuals and groups have been marginalized and discriminated against because of their culture, race, ethnicity, gender, sexual orientation, age, disability, socioeconomic status, appearance, and more. Inclusive language seeks to treat all people with respect, dignity, and impartiality. It is constructed to bring everyone into the group and exclude no one. It is suggested that the basis of communication is not what is said, but how the words are heard. Language framed by derogatory names and symbols can have implications for people and their life experiences [3]. Making changes to use more inclusive language offers us a chance to grow and become better communicators who care for those we are communicating with [4]. This short article is meant to review the concept of political correctness and inclusive language and raise awareness for students and teachers to discriminatory terms that can be easily replaced with clearer and less-offensive alternatives. This topic has been vastly discussed in social sciences and a great number of theories and articles have shed light on the importance of this topic. The goal of this paper is to communicate these ideas to a larger audience including educators in applied sciences including Science, Technology, Engineering and Math (STEM).